The Photometric Variability and Spectrum of the Hot Post-AGB Star IRAS 21546+4721 - Natalia Ikonnikova; Marina Burlak; Alexander Dodin (Galaxies)
We present the results of photometric and spectroscopic observations of a poorly studied B-type supergiant with infrared excess, the hot post-AGB star IRAS 21546+4721. Based on our photometric observations in the <semantics>UBVRCIC</semantics> bands, we detected rapid, night-to-night, non-periodic brightness variations in the star with peak-to-peak amplitudes up to <semantics>0.m3</semantics> in the V band, as well as color–color and color–brightness correlations. Based on its variability characteristics, IRAS 21546+4721 appears similar to other hot post-AGB stars. Possible causes of the photometric variability are discussed. Additionally, we acquired low-resolution spectra in a wavelength range from 3500 to 7500 Å. The spectrum contains absorption lines typical of an early B-type star, along with a set of emission lines of H I, He I, [O I], [O II], [N II], [S II], and C II originating from an ionized circumstellar envelope. An analysis of the emission spectrum allowed us to estimate the parameters of the gas envelope (<semantics>Ne</semantics>∼ 104 cm−3, <semantics>Te</semantics>∼ 10,000 K) and the star’s temperature (∼26,500 K). The radial velocity measured from the emission lines was <semantics>Vr=−141±7</semantics> km s−1.